Customer journey: a customer experience and decision making tool in the e-commerce context - Petra, Mafalda Melo Gouveia (2016)
The subject of Customer Experience has been getting greater projection as consumers are getting more informed, demanding and attentive to their surroundings and so businesses from all industries have felt the urgency to work on this aspect. Particularly in the Continente Online context, the need to study customers buying behavior, in order to meet their expectations and needs, is identified a priority. In this sense, this project aims to create a tool that aggregates all the information available on the Continente Online customers shopping experience, making it visible and clear to the organization - showing the experience through the eyes of the customer. The project's value proposition is based on the creation of a tool, the Customer Journey Map, following the best practices identified in the literature and by experts of Customer Experience, as well as on its application to the business context. This application involves the definition of critical variables for analysis, the definition of the most relevant sources of information and the construction of a knowledge activation methodology emanating from the map. This knowledge will allow the definition of projects that respond to the problems identified on the map (pain points), as well as the activation and promotion of magic moments identified by customers. The ultimate goal is that this holistic knowledge of the experience allows the identification of its pain points and magic moments through its representation in a decision-making process fitted to the customer needs.